2022
DOI: 10.3389/fonc.2022.997457
|View full text |Cite
|
Sign up to set email alerts
|

Hsa-miR-133a-3p, miR-1-3p, GOLPH3 and JUP combination results in a good biomarker to distinguish between prostate cancer and non-prostate cancer patients

Abstract: The incidence and mortality of Prostate Cancer (PCa) worldwide correlate with age and bad dietary habits. Previously, we investigated the mRNA/miRNA role on PCa development and progression using high fat diet (HFD) fed mice. Here our main goal was to investigate the effect of HFD on the expression of PCa-related miRNAs and their relevance in PCa patients. We identified 6 up- and 18 down-regulated miRNAs in TRAMP-C1 mice prostate tumors under HFD conditions using miRNA microarrays. Three down-regulated miRNAs: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Research has found that hypermethylation of the miR-1-2 gene (the gene coding miR-1-3p) promoter reduces the expression of miR-1-3p in prostate cancer. The decrease in miR-1-3p expression promotes the invasive ability of prostate cancer cells, which may be related to targeting downstream genes GOLPH3 and JUP [ 45 ]. Zhou et al found that circSKA3 could increase the methylation of the miR-1 gene in glioblastoma, thereby reducing the expression of miR-1, and promoting the proliferation of glioblastoma cells [ 46 ].…”
Section: Production and Regulation Of Mir-1-3pmentioning
confidence: 99%
“…Research has found that hypermethylation of the miR-1-2 gene (the gene coding miR-1-3p) promoter reduces the expression of miR-1-3p in prostate cancer. The decrease in miR-1-3p expression promotes the invasive ability of prostate cancer cells, which may be related to targeting downstream genes GOLPH3 and JUP [ 45 ]. Zhou et al found that circSKA3 could increase the methylation of the miR-1 gene in glioblastoma, thereby reducing the expression of miR-1, and promoting the proliferation of glioblastoma cells [ 46 ].…”
Section: Production and Regulation Of Mir-1-3pmentioning
confidence: 99%